The Comparision of the Effectiveness of Short Wave Diathermy and Ultrasound in the Treatment of Gonarthrosis - Banu Sarıfakıoğlu; Aliye Yıldırım Güzelant; Erkan Özduran (Galenos Yayinevi, 2014)
Objective: To compare the efficacy of ultrasound (US) and short wave diathermy (SWD) in the gonarthrosis patients. Materials and Methods: Patients who had been diagnosed gonarthrosis according to American College of Rheumatology (ACR) classification criteria were included into the study. Patients who have undergone knee surgery, had trauma, had knee injection into the knee in the last six months, and had received physical therapy (PT) in the past year were excluded from the study. Patients were divided into two groups (US group and SWD group). HP (20 min), US (1.5 w/cm2, continuous), TENS (20 min), exercise were administered to the first group. HP (20 min), SWD (15 min), TENS (20 min), exercise were implemented to the second group. PT was administered for five days a week, for 15 sessions in total. Visual analog scale (VAS) and Western Ontario and MacMaster osteoarthritis index (WOMAC) were used to assess function and pain before and after PT. Results: 132 patients were included into the study, 63 patients (47.7%) were in SWD group, and 69 patients (52.3%) were in US group. There were no statistically difference between the VAS, WOMAC values of the groups before and after PT. In both groups, VAS, WOMAC were scores statistically significantly decreased with treatment (all p<0.001). Conclusion: This study showed that both these PT modalities are effective in treating the gonarthrosis, but not superior to each other. (Turkish Journal of Osteoporosis 2014;20: 16-20)